2016
DOI: 10.1057/ejis.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Representing small business web presence content: the web presence pyramid model

Abstract: This article investigates 'stage' models that have been developed for researchers, practitioners and policymakers to explain how small businesses move from a basic to a sophisticated online presence and/or provide advice as to how they could do this. The main problem of these models is that small businesses do not necessarily develop their online presence in this manner. In addition, they do not consider that the online presence of most small businesses extends beyond their own website to the use of third part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…Regarding their presence on the Internet, new Burgess Classification [79] was used, where the presence of a business on the Internet is classified in a pyramid depending on its web model. To this categorization was added the percentage of the volume of online sales over the total sales.…”
mentioning
confidence: 99%
“…Regarding their presence on the Internet, new Burgess Classification [79] was used, where the presence of a business on the Internet is classified in a pyramid depending on its web model. To this categorization was added the percentage of the volume of online sales over the total sales.…”
mentioning
confidence: 99%
“…The study adopted a survey approach to analyze the web presence of local sporting clubs, similar to that adopted by Burgess (2016).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Lopes and Melão (2016) study of Portuguese SME websites found mostly simple websites, with only 16% accepting online orders or reservations and 6% facilitating online payments. Additionally, Burgess (2016) noted that stage models mostly concentrated only upon small business websites, not including other aspects of the small business web presence. Burgess (2016) developed the web presence pyramid model (refer Figure 1) to represent Australian small business' broader web presence.…”
Section: Sme Web Presence Modelsmentioning
confidence: 99%
See 2 more Smart Citations